The Impact of Corruption on Domestic Economic Activity - Pluskota, Anna Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The purpose of this article is to analyze the impact of corruption on entrepreneurship. The relationship between corruption and entrepreneurship is undoubtedly observed, but its characterization in literature (mainly foreign) is poor. The following article is an attempt to describe the most important correlations between corruption and entrepreneurship and the functioning of companies under the conditions of corrupt officials. The study was carried out by analyzing available literaturę as well as the available data to construct econometric models verifying the hypothesis of a nonlinear (concave) relationship between corruption and entrepreneurship. The study was conducted on data collected for 28 European countries. On the basis of the analysis of literature and econometric studies it was found that the relationship between corruption and entrepreneurship is nonlinear (concave). The best result was obtained for a model with logarithm of the corruption index, which was characterized by better values of selected statistics. An interesting description of the analysis made is a structured description of the relationship between corruption and entrepreneurship, which was assessed in each case. On the basis of literature analysis, the characteristics of the concave relationship between corruption and entrepreneurship are described, which points to the diminishing benefits of combating corruption for economic development.